The journal of the Reverend William Impey, 1838-1847 : a critical study of his work and theology - Owen, David Rhys (Rhodes University, Faculty of Divinity, Department of Divinity, 1993)
William Impey (1818-1896) came to South Africa as a Wesleyan Methodist Missionary in 1839. He held various missionary and colonial appointments until 1860 when he succeeded William Shaw as Chairman of the Albany and Kaffraria District and General Superintendent of Wesleyan Methodist Missions in South-East Africa. Impey's major contribution was in the provision of education for the indigenous peoples of this region, especially as President of Healdtown (1868-1878). This institution eventually became one of the most highly thought of mission education academies in South Africa. To date little has been known of the life and work of William Impey despite his senior position in South African Wesleyan Methodism. J Whiteside's History of the Wesleyan Methodist Church of South Africa, the last comprehensive history of South African Methodism, published in 1906, only devotes a few lines to Impey. He does however make further reference to Impey's work in his section on education. The Methodist Archive at Manchester University, which contains the personal records of all 19th century Wesleyan Methodist ministers, also has very little information about Impey. The reason for this relative lack of information is that he resigned from the Wesleyan Methodist Church in 1878 on doctrinal grounds. Impey came under the influence of 19th century liberal theology and eventually drew the conclusion that he could no longer accept the doctrine of 'eternal punishment'. He believed that the only honest thing for him to do was to resign from the Wesleyan Methodist Church, which he believed required its ministers to adhere to this doctrine. He was accepted for ordination by the Anglican Church and served as a deacon in 1878 and then as a priest until his death in 1896. Impey's journal affords the reader an opportunity to have a glimpse into what life was like for a 19th century missionary living and working in South Africa. Perhaps its particular value lies in the many detailed entries Impey made about his personal spiritual experiences. The aim of this thesis is to place the life's work of William Impey in its historical and theological context in the belief that this will enable us better to understand the 19th century missionaries. It is hoped that this study will make a further contribution to our understanding of both 19th century missionaries and the times in which they lived and worked.
Keywords: Impey, William, 1818-1896; Methodist Church of Southern Africa -- Clergy -- Biography; Methodist Church -- Missions; Missionaries -- Biography